A NOVEL SYNTHETIC PROTOCOL FOR THE BIS-TRIAZOLONES DERIVATIVES THROUGH CORRESPONDING N1-ETHOXYCARBONYL-N1-TOSYLHYDRAZONATES (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
A simple method has been developed for the synthesis of bis-triazolones 2a-n starting from N1-ethoxycarbonyl-N1-tosylhydrazonates 1 and aliphatic diamine. It affords a number of bis-triazolones 2a-nÂ  in reasonable yields. The structures of all new compounds were elucidated using infrared, 1H and 13C NMR studies as well as elemental analysis. Some of these reactions provide successful means to produce biologically important structures.